The correlation between workload and nurse performance during the covid-19 pandemic at hospital - Rizki Yeni Wulandari; Adi Prasandi; Tri Adi Nugroho; Noverita Gusmeta (Universitas Aisyah Pringsewu, 2023)
High work demands because the provision of nursing care is carried out 24 hours a day with patients who require special care. This activity causes the work of nurses to increase and can increase the physical workload of nurses. Based on a preliminary study of 10 nurses, it was found that as many as 8 people (80%) stated that the workload they carried out was heavy. The research objective was to determine the correlation between workload and nurse performance during the Covid 19 pandemic at the Muhammadiyah Metro Hospital. This research used a quantitative method, with a cross-sectional approach. The sample used in this study amounted to 164 respondents by taking the total sampling technique. The analysis used is Spearman Rho. The research result showed that there is a correlation between workload and nurse performance during the Covid 19 pandemic at the Muhammadiyah Hospital in Metro City P-value = 0.000 with a correlation strength of 0.475, which is included in the moderate or sufficient correlation. It is recommended for hospitals to pay attention to the workload given by nurses when patients are overloaded so, the nurses do not experience a workload that is too heavy. It can be done by increasing service capacity and human resources. Abstrak: Tuntutan kerja yang tinggi karena pemberian asuhan keperawatan dilakukan selama 24 jam setiap hari dengan pasien yang memerlukan perawatan khusus. Aktivitas inilah yang menyebabkan kerja perawat menjadi meningkat dan dapat menambah beban kerja fisik perawat. Berdasarkan studi pendahuluan dari 10 perawat diperoleh gambaran bahwa sebanyak 8 orang (80%) menyatakan bahwa beban kerja yang dilaksanakannya yaitu berat. Tujuan penelitian ini mengetahui hubungan beban kerja dengan kinerja perawat masa pandemi Covid 19 di Rumah Sakit Muhammadiyah Metro. Penelitian ini menggunakan metode kuantitatif, dengan pendekatan crossectional sampel yang digunakan dalam penelitian ini berjumlah 164 responden dengan mengambil teknik teknik total sampling. Analisis yang digunakan menggunakan spearman rho. Hasil penelitian diketahui. Ada hubungan beban kerja dengan kinerja Perawat pada masa pandemi Covid 19 di Rumah Sakit Muhammadiyah Kota Metro P value = 0,000 dengan kekuatan korelasi sebesar 0,475 masuk dalam korelasi sedang atau cukup. Disrankan bagi rumah sakit agar memperhatikan beban kerja yang diberikan oleh perawat ketika pasien sedang overload, sehingga perawat tidak mengalami beban kerja yang terlalu berat, dengan cara menambah kapasitas pelayanan dan SDM.